Design and safe operation of photovoltaic installations - Włodarczyk, Renata (Instal, 2023)
The market of photovoltaic installations in Poland is a dynamically developing sector of renewable energy, which is to counteract climate pollution and help in the pursuit of increasing energy efficiency. Renewable energy cooperating with modern hydrogen technologies will soon be an innovative energy storage. According to data prepared by the Institute of Renewable Energy (IRE), the installed capacity of photovoltaics in Poland in 2021 amounted to 7.6 GW, and the total turnover on the PV market was estimated at PLN 16.7 billion. Individual prosumers had the largest share in the increase in installed capacity. According to IRE forecasts, the growth dynamics of photovoltaic installations will continue in the coming years thanks to the increase in capacity in PV farms. There will be more and more investors interested in building micro-installations and installations with higher capacity, which is why it is important what the investor should pay attention to at the stage of designing the installation and its use. This article will discuss the various stages of creating an installation: from site recognition, selection of components, design and assembly, to commissioning and safe operation of the installation. The work discusses the most common problems that can be encountered in individual households equipped with photovoltaic panels and what effects and consequences they can cause.